Fitness problem in shift workers while adjusting in ever changing working schedule - Soni, Rakesh Kumar (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> The present study was aimed to assess the diurnal variations in few physiological processes in rotational shift workers suffering irregular life styles due tohaving regular and/or irregular workload during night shift. The diurnal variations in rest-activity was monitored, using wrist actigraphy, in cohorts of 14 shift workers (SWs) employed in the Sponge Iron Manufacturing Industry (SIMI) and 20 shift workers (SWs) of the Chhattisgarh State Electricity Board (CSEB). The former organization adopts regular rotational shift system and the latter an irregular rotational shift pattern. SWs of both organizations worked in a counterclockwise 3-shift system. All SWs were provided an actiwatch around the clock covering all three shifts to monitor their sleep-wake activity pattern. One-minute epoch length was chosen for collection of wrist actigraphy data. Data were analyzed using computations of dichotomy index (I<O) and autocorrelation coefficient (r24). The irregular rotational SWs from CSEB took rest/ nap/ sleep in the night shift while on duty. Therefore, the activity pattern of these subjects was somewhat similar to that of the day workers. Results of the present study showed that autocorrelation coefficient was significantly (p < 0.05) lower in irregular rotational shift workers as compared to regular rotational shift workers only during the morning shift. There are no statistically significant differences between the means of r24 obtained for the morning, afternoon, and night shifts, when values were compared separately for each organization. Further, the regular rotational SWs exhibited significantly lower dichotomy index during night shift as compared to morning shift. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->